Regulation of Natural mRNAs by the Nonsense-Mediated mRNA Decay Pathway - Peccarelli, Megan (American Society for Microbiology, 2014)
The nonsense-mediated mRNA decay (NMD) pathway is a specialized mRNA degradation pathway that degrades select mRNAs. This pathway is conserved in all eukaryotes examined so far, and it triggers the degradation of mRNAs that prematurely terminate translation. Originally identified as a pathway that degrades mRNAs with premature termination codons as a result of errors during transcription, splicing, or damage to the mRNA, NMD is now also recognized as a pathway that degrades some natural mRNAs. The degradation of natural mRNAs by NMD has been identified in multiple eukaryotes, including Saccharomyces cerevisiae, Drosophila melanogaster, Arabidopsis thaliana, and humans. S. cerevisiae is used extensively as a model to study natural mRNA regulation by NMD. Inactivation of the NMD pathway in S. cerevisiae affects approximately 10% of the transcriptome. Similar percentages of natural mRNAs in the D. melanogaster and human transcriptomes are also sensitive to the pathway, indicating that NMD is important for the regulation of gene expression in multiple organisms. NMD can either directly or indirectly regulate the decay rate of natural mRNAs. Direct NMD targets possess NMD-inducing features. This minireview focuses on the regulation of natural mRNAs by the NMD pathway, as well as the features demonstrated to target these mRNAs for decay by the pathway in S. cerevisiae. We also compare NMD-targeting features identified in S. cerevisiae with known NMD-targeting features in other eukaryotic organisms.